Machado-Joseph Deubiquitinases: From Cellular Functions to Potential Therapy Targets - Chenming Zeng; Chenxi Zhao; Fujing Ge; Yuekang Li; Ji Cao; Meidan Ying; Jinjian Lu; Qiaojun He; Bo Yang; Xiaoyang Dai; Hong Zhu (Frontiers Media S.A., 2020)
Ubiquitination is known as important post-translational modification in cancer-related pathways. Human deubiquitinases (DUBs), with functions of modulating the ubiquitination process, are a family with about 100 proteins. They mainly function by cutting ubiquitin chains of the substrates. The Machado-Joseph domain-containing proteases (MJDs) is one of the sub-families of DUBs, consisting of four members, namely, Ataxin-3, Ataxin-3L, JOSD1, and JOSD2. Recent studies have provided new insights into biological functions of MJDs in the progression of Machado-Joseph disease or cancer diseases. In this review, we summarized the cellular functions and regulatory mechanisms of MJDs in Machado-Joseph disease and cancer pathways. Furthermore, we summarized MJDs genetic alterations in different human cancers by exploring the public databases (cBioportal). The aim of this review is to provide a comprehensive account based on our current knowledge about emerging insights into MJDs in physiology and disease, which might shed light on fundamental biological questions and promise to provide a potential target for therapeutic intervention.